Antimicrobial effect of hydroalcoholic extract of Allium sativum strains on standards of the oral cavity - Munayco Pantoja, Evelyn (2013)
The aim of this study was to determine the antimicrobial and antifungal effect of Allium sativum extract against ATCC strains of S. mutans, Capnocytophaga sputigena, Lactobacillus casei and C. albicans at various concentrations. The extract was obtained by the mashing process and the experimental test, was used by disk diffusion method: ciprofloxacin and fluconazole as positive control of bacteria and fungi, respectively and alcohol 70 as a negative control. When performing susceptibility testing with the extract at concentrations of 12mg/ml, 18mg/ml 30mg/ml, 60mg/mL, 90mg/mL, 120mg/mL, we obtained the following results: The antimicrobial concentration versus sputigena Capnocytophaga, Streptococcus mutans and Candida albicans, was 120mg/mL, taking as reference standard to ciprofloxacin at a concentration of 4mg/ml and fluconazole at a concentration of 2mg/ml. Concluded that the hydroalcoholic extract of Allium sativum presented antimicrobial effect against S. strain ATCC mutans, Capnocytophaga sputigena, and C. albicans except that showed resistance Lactobacillus casei.